1979
DOI: 10.1007/bf02441182
|View full text |Cite
|
Sign up to set email alerts
|

Radioautographic visualization of3H-fucose incorporation into glycoprotein by osteoblasts and its deposition into bone matrix

Abstract: Summary. The elaboration of bone matrix glycoprotein by osteoblasts of alveolar bone was investigated by radioautography after the intravenous injection of 3H-fucose into young rats. At selected times after injection, animals were sacrificed by intracardiac perfusion and demineralized specimens were prepared for light and electron microscope radioautography.At 5 and 10 min after injection, when the blood fucose level was high, silver grains were restricted to the spheroidal and cylindrical saccules of the Golg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…creted in tandem via the same pathway or whether a separate population of secretory granules and a separate exocytotic pathway exist specifically for these proteins. Here, it should be emphasized that the often misquoted early radioautographic studies by Weinstock et al (251,252,255) on bone and teeth demonstrated phosphoprotein and/or glycoprotein deposition into prebone (osteoid) and predentin, fol-lowed by its subsequent accumulation at the mineralization front in these tissues. Thus, as shown for collagen, the release of noncollagenous proteins appears to occur primarily at the base of osteoblast (and odontoblast) cell processes and from the cell body itself.…”
Section: Fig 2 Transmission Electron Micrographs Of Cells Extra-dumentioning
confidence: 93%
“…creted in tandem via the same pathway or whether a separate population of secretory granules and a separate exocytotic pathway exist specifically for these proteins. Here, it should be emphasized that the often misquoted early radioautographic studies by Weinstock et al (251,252,255) on bone and teeth demonstrated phosphoprotein and/or glycoprotein deposition into prebone (osteoid) and predentin, fol-lowed by its subsequent accumulation at the mineralization front in these tissues. Thus, as shown for collagen, the release of noncollagenous proteins appears to occur primarily at the base of osteoblast (and odontoblast) cell processes and from the cell body itself.…”
Section: Fig 2 Transmission Electron Micrographs Of Cells Extra-dumentioning
confidence: 93%
“…x 10,000, exclusively in the Golgi apparatus of intestinal columnar and goblet cells ( Fig. 4) (Bennett and Leblond, 1970;Michaels and Leblond, 1976), hepatocytes (Bennett and , and the great majority of other cell types (Bennett, 1978;Bennett and Haddad, 1986;Brasileiro et al, 1982;Garant, 1985, 1986;Ginsel et al, 1979;Haddad et al, 1971Haddad et al, , 1977Haddad andBennett, 1987, 1988;Hand, 1979;Lima and Haddad, 1981;Rougier, 1976;Weinstock et al, 1972;Weinstock, 1979). In some exceptional cell types, a significant uptake of 'H-fucose label at the level of the rough endoplasmic reticulum was also noted (Pelletier and Puviani, 1973;Pelletier, 1974;Samuel and Flickinger, 1986).…”
Section: Figmentioning
confidence: 99%
“…In contrast, little is known about the synthesis and secretion of non-collagenous glycoproteins from POL fibroblasts. Tritiated fucose has been used in radioautographic studies of the secretion of non-collagenous matrix components from odontoblasts and osteoblasts (Weinstock, Weinstock & Leblond, 1972, Weinstock 1979. In odontoblasts and osteoblasts, 3H-fucose was rapidly incorporated into spheroidal saccules of the Golgi apparatus at 5 to 10 minutes after injection.…”
Section: Introductionmentioning
confidence: 99%